Mergers and acquisitions of Malaysian banks. - Lim, Sze Thien. (2008)
Using an event study methodology, this study seeks to determine whether and how the market reacts to the announcements of the M&A programme. Empirical studies are carried out to examine investors’ reaction towards the M&A announcements and the effect on shareholders’ returns of the different banking institutions involved.